Perceptions of old age and transition to retirement of older adults (Práxis Educativa, 2023)
The increase in average life expectancy led to an increase in the older adult population. Thus, this text aims to analyze perceptions about old age and transitions to retirement in older adults. Empirical data resulted from a biographical investigation carried out with six retired adults, through biographical interviews. The conceptual framework adopted focuses on life stories and biographical transitions, in aging, old age and retirement, and experiential learning. Retired adults participating in the research show a tendency to associate aging and old age with disability and inactivity. The transition to retirement is experienced in multiple ways, according to the experience and uniqueness of each adult. However, there is a widespread attempt to preserve autonomy, self-recognition and identity. In the experience of late adulthood, the person value essential skills for life such as the power to speak, the power to narrate and the power to act.Keywords: Older adult people. Transition. Retirement.